Cognitive function after two doses of cranial irradiation for acute lymphoblastic leukaemia. Issue 10 (October 1991) - Rodgers, J; Britton, P G; Kernahan, J; Craft, A W
Abstract : The cognitive function of 23 children given cranial irradiation in a dose of 24 Gy was compared with that of 41 given 18 Gy. No significant differences were found in intellectual function or in mean number of intelligence quotient points lost between patients in the two treatment groups. A reduction in the dose of cranial irradiation does not seem to alleviate long term neuropsychological deficits.